Seasonal influenza vaccine effectiveness against medically attended influenza illness among children aged 6–59 months, October 2011–September 2012: A matched test-negative case–control study in Suzhou, China. Issue 21 (5th May 2016) - Wang, Yin; Zhang, Tao; Chen, Liling; Greene, Carolyn; Ding, Yunfang; Cheng, Yuejia; Yang, Chao; Zeng, Shanshan; Hua, Jun; Zhou, Suizan; Song, Ying; Luan, Lin; et al.
Abstract: Background: Seasonal influenza infections among young children in China lead to substantial numbers of hospitalizations and financial burden. This study assessed the seasonal influenza vaccine effectiveness (VE) against laboratory confirmed medically attended influenza illness among children in Suzhou, China, from October 2011–September 2012. Methods: We conducted a test-negative case–control study among children aged 6–59 months who sought care at Soochow University Affiliated Children's Hospital (SCH) from October 2011–September 2012. A case was defined as a child with influenza-like illness (ILI) or severe acute respiratory infection (SARI) with an influenza-positive nasopharyngeal swab by rRT-PCR. Controls were selected from children presenting with ILI or SARI without laboratory confirmed influenza. We conducted 1:1 matching by age and admission date. Vaccination status was verified from the citywide immunization system database. VE was calculated with conditional logistic regression: (1 − OR) × 100%. Result: During the study period, 2634 children aged 6–59 months presented to SCH with ILI (1975) or SARI (659) and were tested for influenza. The vaccination records were available for 69% (1829; ILI: 1354, SARI: 475). Among those, 23% (427) tested positive for influenza, and were included as cases. Among influenza positive cases, the vaccination rates were 3.2% for SARI and 4.5% for ILI. Among controls, the vaccination rates were 13% for SARI, and 11% for ILI. The overall VE against lab-confirmed medically attended influenza virus infection was 67% (95% CI: 41–82). The VE for SARI was 75% (95% CI: 11–93) and for ILI was 64% (95% CI: 31–82). Conclusions: The seasonal influenza vaccine was effective against medically attended lab-confirmed influenza infection in children aged 6–59 months in Suzhou, China in the 2011–12 influenza season. Increasing seasonal influenza vaccination among young children in Suzhou may decrease medically attended influenza-associated ILI and SARI cases in this population.